Prime incision: A minimally invasive approach to breast cancer surgical treatment-A 2 cohort retrospective comparison with conventional breast conserving surgery. - Silvio Eduardo Bromberg; Patricia Rodrigues Alves de Figueiredo Moraes; Felipe Ades (PLoS ONE, 2018)
The prime incision technique is an oncoplastic surgery aimed to remove both the breast tumor and the sentinel lymph node through one incision, thus providing better aesthetic results than the conventional breast conservative two incision technique. We retrospectively evaluated 2 cohorts of 60 consecutive breast cancer patients operated by either conventional breast conservative surgery (N = 26) or one incision surgery (N = 34). There were no recurrence or death events observed in any group. No difference was seen regarding the incidence of surgical complications. In the prime incision group the breast volume removed was significantly lower than in the conventional surgery group as well as was the surgical time and the number of dissected lymph nodes. Aesthetical results were better in the one incision group. Further prospective studies are needed to validate the one incision technique as a surgical option for selected early stage breast cancer patients.